2020
DOI: 10.1016/j.xplc.2020.100040
|View full text |Cite
|
Sign up to set email alerts
|

Multifaceted Signaling Networks Mediated by Abscisic Acid Insensitive 4

Abstract: Although ABSCISIC ACID INSENSITIVE 4 (ABI4) was initially demonstrated as a key positive regulator in the phytohormone abscisic acid (ABA) signaling cascade, multiple studies have now shown that it is actually involved in the regulation of several other cascades, including diverse phytohormone biogenesis and signaling pathways, various developmental processes (such as seed dormancy and germination, seedling establishment, and root development), disease resistance and lipid metabolism. Consistent with its versa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
64
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(64 citation statements)
references
References 88 publications
0
64
0
Order By: Relevance
“…ABI4, which was initially demonstrated to be a key positive regulator in the ABA signaling transduction pathway (Finkelstein et al ., 1998; Soderman et al ., 2000), has been shown to act as a versatile transcription factor involved in diverse crosstalk networks with other phytohormones, plant development periods and also in abiotic/biotic stress responses (Kong et al ., 2013; Shu et al ., 2013, 2016a,b, 2018; Wind et al ., 2013; Li et al ., 2014; Lee et al ., 2015; Dong et al ., 2016; Guo et al ., 2016; Xie et al ., 2016; Xu et al ., 2016; Huang et al ., 2017; Cheng et al ., 2018; Yan et al ., 2019; Chandrasekaran et al ., 2020). It should be noted that an early study showed that ABI4 is essential for ascorbic acid (AsA)‐mediated plant growth and jasmonate‐dependent defense signaling (Kerchev et al ., 2011).…”
Section: Introductionmentioning
confidence: 99%
“…ABI4, which was initially demonstrated to be a key positive regulator in the ABA signaling transduction pathway (Finkelstein et al ., 1998; Soderman et al ., 2000), has been shown to act as a versatile transcription factor involved in diverse crosstalk networks with other phytohormones, plant development periods and also in abiotic/biotic stress responses (Kong et al ., 2013; Shu et al ., 2013, 2016a,b, 2018; Wind et al ., 2013; Li et al ., 2014; Lee et al ., 2015; Dong et al ., 2016; Guo et al ., 2016; Xie et al ., 2016; Xu et al ., 2016; Huang et al ., 2017; Cheng et al ., 2018; Yan et al ., 2019; Chandrasekaran et al ., 2020). It should be noted that an early study showed that ABI4 is essential for ascorbic acid (AsA)‐mediated plant growth and jasmonate‐dependent defense signaling (Kerchev et al ., 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Abscisic acid (ABA) is a key phytohormone, which plays versatile functions in developmental regulation and various environmental stress response. The ABA plays roles in spatiotemporal and dose-dependent ways, which is connected with its diverse functions ( Liu et al, 2019 ; Lu et al, 2019 ; Chandrasekaran et al, 2020 ; Xie et al, 2020 ). ABA is well-known for its stress-related properties, but it also has been proven to regulate plant growth and development such as seed germination, root growth and flowering transition ( Huang et al, 2017 ; Belda-Palazon et al, 2018 ; Xiong et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…A subset of key genes involved in ABA signaling has been identified. Among these genes, ABA INSENTIVE ( ABI ) 1 , ABI2 , ABI3 , ABI4 , and ABI5 , encode five key negative or active regulators of ABA response ( Leung et al, 1997 ; Skubacz et al, 2016 ; Chandrasekaran et al, 2020 ). ABI1 and ABI2 encode type 2C protein phosphatases (PP2Cs) that play roles as negative regulators of ABA signaling.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations